On the strategies and functions of closings in political discourse - Cortés Rodríguez, Luis; Herrero Muñoz-Cobo, Bárbara (Romanica Olomucensia, 2014)
Closings in political discourses promote rhetorical strategies in order to make the message conveyed more credible as well as to better capture the audience attention. This article, drawing on all the speeches of the Presidents of the Spanish Government and the opposition leaders, analyses some of the strategies deployed in these speeches. While it is true that the differences in the closings by Presidents and opposition leaders are significant in terms of its subject matter, it should nonetheless be noted that similar oratory devices are used, such as longer pauses, anaphora, concessio, overlooking or paralypsis and, in particular, enumerative lists, a key rhetorical figure in political discourse. This paper furnishes a detailed analysis of these devices and their functions.
Keywords: discourse analysis; political discourse; discursive mechanisms; oral discourse.